INTEGRATING LOCAL CULTURE AND ISLAMIC EDUCATION FOR CONTEXTUAL CHARACTER IN WEST SUMATRA - Rego, Dipalpa; Kustati, Martin; Bashori; Rahman Suyatno, Harif (As-Sulthan Journal of Education, 2025)
The phenomenon of moral degradation and character crisis among the younger generation demands a transformation of Islamic education to become more contextual and rooted in local culture. This article aims to examine a new paradigm of integrating Minangkabau culture and Islamic education in shaping contextual character in West Sumatra. The study employs a qualitative method through library research and content analysis of relevant literature on ethnopedagogy, the philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah”, and Islamic educational theory. The findings reveal that integrating local values such as deliberation (musyawarah), modesty (malu), and mutual cooperation (gotong royong) with Islamic principles such as syura, al-hayā’, and ta’awun produces an educational model that is religious, humanistic, and adaptive to social dynamics. Islamic education based on local wisdom strengthens cultural identity, shapes moral character, and promotes religious moderation and social harmony. This paradigm affirms that Islam is not merely a theological norm but a living culture that guides the formation of insan adabi the civilized human. Therefore, the integration of Minangkabau cultural values and Islamic education offers a contextual educational model relevant to strengthening the moral and spiritual foundation of the younger generation in the global era.